Goal orientation and academic self-concept of children with self-handicapping behavior - Pidlaoan, Karen C.; Oligario, Lizamarie Campoamor; Oael, Irene C.; Vinluan, Lorelei R. (Quezon City College of Education, University of the Philippines Diliman, 2015)
" The research primarily aimed at describing the self-handicapping behavior, the goal orientation and academic self-concept of children with self-handicapping behavior. Specifically it aimed at identifying the self-handicapping behaviors of the children as perceived by the children themselves; and as perceived by teachers, parents and guidance counselors; the goal orientations of the children with self-handicapping behavior; the academic self-concept level of the children with self-handicapping behavior in terms of academic confidence and academic effort; and the relationship between goal orientation and self-handicapping behavior; academic self-concept and self-handicapping behavior; and goal orientation and academic self-concept.
The quantitative-qualitative study revealed the following outcomes: Self-handicapping behaviors can either be in the self-reported form or in behavioral form and based on the psychological, physiological, motivational and family-related behaviors. The most prevalent goal orientation of the children with self-handicapping behavior is the mastery goal orientation followed by performance avoidance goal orientation and lastly performance approach goal orientation. Based on their academic self-concept level, the students with self-handicapping behavior had slightly higher concept of their academic effort than their academic competence. The level of self-concept was not very high, which supports previous research on self-handicapping. There is a relationship between goal orientation and self-handicapping behavior; academic self-concept and self-handicapping behavior; and goal orientation and academic self-concept." --
Thesis
Keywords: Self-defeating behavior; Children with disabilities -- Education -- Philippines -- Quezon City; Behavior disorders in children -- Philippines -- Quezon City